Adaptation and Phenotypic Diversification in Arabidopsis through Loss-of-Function Mutations in Protein-Coding Genes. Issue 5 (18th March 2019) - Xu, Yong-Chao; Niu, Xiao-Min; Li, Xin-Xin; He, Wenrong; Chen, Jia-Fu; Zou, Yu-Pan; Wu, Qiong; Zhang, Yong E.; Busch, Wolfgang; Guo, Ya-Long
Abstract : A large-scale study exploring how gene loss contributes to evolutionary change reveals that loss-of-function mutations contribute to the adaptation and phenotypic diversification of plants. Abstract: According to the less-is-more hypothesis, gene loss is an engine for evolutionary change. Loss-of-function (LoF) mutations resulting in the natural knockout of protein-coding genes not only provide information about gene function but also play important roles in adaptation and phenotypic diversification. Although the less-is-more hypothesis was proposed two decades ago, it remains to be explored on a large scale. In this study, we identified 60, 819 LoF variants in 1071 Arabidopsis ( Arabidopsis thaliana ) genomes and found that 34% of Arabidopsis protein-coding genes annotated in the Columbia-0 genome do not have any LoF variants. We found that nucleotide diversity, transposable element density, and gene family size are strongly correlated with the presence of LoF variants. Intriguingly, 0.9% of LoF variants with minor allele frequency larger than 0.5% are associated with climate change. In addition, in the Yangtze River basin population, 1% of genes with LoF mutations were under positive selection, providing important insights into the contribution of LoF mutations to adaptation. In particular, our results demonstrate that LoF mutations shape diverse phenotypic traits. Overall, our results highlight the importance of the LoF variants for the adaptation and phenotypic diversification of plants.